Valuing intellectual capital : multinationals and taxhavens - Wiederhold, Gio (Management for Professionals,, 2014)
Valuing Intellectual Capital provides readers with prescriptive strategies and practical insights for estimating the value of intellectual property (IP) and the people who create that IP within multinational companies.  This book addresses the crucial topic of taxation from a rigorous and quantitative perspective, backed by experience and original research that illustrates how large corporations need to measure the worth of their intangible assets.  Each method in the text is applied through the lens of a model corporation, in order for readers to understand and quantify the operation of a real-world multinational enterprise and pinpoint how companies easily misvalue their intellectual capital when transferring IP rights to offshore tax havens.  The effect contributes to the issues that can lead to budgetary crises, such as the so-called "fiscal cliff" that was narrowly averted by passage of the American Taxpayer Relief Act on New Year's Day 2013. This book also features a chapter containing recommendations for a fair and balanced corporate tax structure free of misvaluation and questionable mechanisms. CFOs, corporate auditors, corporate financial analysts, corporate financial planners, economists, and journalists working with issues of taxation will benefit from the concepts and background presented in the book. The material clearly indicates how a trustworthy valuation of intellectual capital allows a realistic assessment of a company's income, earnings, and obligations.  Because of the intense interest in the topic of corporate tax avoidance the material is organized to be accessible to a broad audience. Gio Wiederhold is professor emeritus of Computer Science at Stanford University. He holds a PhD from the University of California, San Francisco and an honorary D.Sc. from the National University of Ireland, Galway. He has been elected as a fellow of the ACM, the IEEE, and the ACMI. Gio has been consulting on technical- and business-related issues since 1965 in government, academia, and industry, including several multinationals in finance, computing, and pharmaceuticals. He currently teaches two courses at Stanford: Business on the Internet and Software Economics.